Measurements of the ionization coefficient of simulated iron micrometeoroids. Issue 8 (27th April 2016) - Thomas, Evan; Horányi, Mihály; Janches, Diego; Munsat, Tobin; Simolka, Jonas; Sternovsky, Zoltan
Abstract: The interpretation of meteor radar observations has remained an open problem for decades. One of the most critical parameters to establish the size of an incoming meteoroid from radar echoes is the ionization coefficient, β, which still remains poorly known. Here we report on new experiments to simulate micrometeoroid ablation in laboratory conditions to measure β for iron particles impacting N2, air, CO2, and He gases. This new data set is compared to previous laboratory data where we find agreement except for He and air impacts > 30 km/s. We calibrate the Jones model of β ( v ) and provide fit parameters to these gases and find agreement with all gases except CO2 and high‐speed air impacts where we observe β air > 1 for velocities > 70 km/s. These data therefore demonstrate potential problems with using the Jones model for CO2 atmospheres as well as for high‐speed meteors on Earth. Key Points: Laboratory measurements of the ionization coefficient of iron in various gases The new data will help to improve the interpretation of meteor radar measurements